2013
DOI: 10.1200/jco.2013.51.1972
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Hypofractionated External-Beam Radiotherapy for Prostate Cancer

Abstract: Purpose To determine if escalated radiation dose using hypofractionation significantly reduces biochemical and/or clinical disease failure (BCDF) in men treated primarily for prostate cancer. Patients and Methods Between June 2002 and May 2006, men with favorable- to high-risk prostate cancer were randomly allocated to receive 76 Gy in 38 fractions at 2.0 Gy per fraction (conventional fractionation intensity-modulated radiation therapy [CIMRT]) versus 70.2 Gy in 26 fractions at 2.7 Gy per fraction (hypofractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
281
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(311 citation statements)
references
References 25 publications
20
281
2
8
Order By: Relevance
“…Randomized studies in breast cancer have shown that delivery can be given in a shorter period of time without effect on overall survival, local control or toxicities compared to standard fractionation (Haviland et al, 2013, Whelan et al, 2010, Owen et al, 2006). Similar findings are being reported in prostate cancer (Kupelian et al, 2007, Hoffman et al, 2014, Pollack et al, 2013). …”
Section: High Priority Topics For Lmicssupporting
confidence: 90%
“…Randomized studies in breast cancer have shown that delivery can be given in a shorter period of time without effect on overall survival, local control or toxicities compared to standard fractionation (Haviland et al, 2013, Whelan et al, 2010, Owen et al, 2006). Similar findings are being reported in prostate cancer (Kupelian et al, 2007, Hoffman et al, 2014, Pollack et al, 2013). …”
Section: High Priority Topics For Lmicssupporting
confidence: 90%
“…Therefore, in the present protocol, we proposed to combine a hypofractionated approach that benefits from the low ˛/ˇ ratio of prostate cancer and the conformality achieved with proton therapy to deliver an abbreviated course of therapy for low-risk prostate cancer. [1][2][3][4][5][6] All patients required image guidance with fiducial placement and magnetic resonance imaging registration. The rationale of this image guidance approach for proton therapy has been reviewed previously.…”
Section: Introductionmentioning
confidence: 99%
“…Dearnaley [38] vizsgála-tában a normo-és hipofrakcionált kezelésben részesült betegek 7,8 és 5,9%-ában alakult ki mérsékelt vagy súlyos gastrointestinalis toxicitás. A Hoffman [42] által publikált RCT-ben ez az arány 5,1% és 10%, míg a Pollack [41] által 2013-ban publikált klinikai vizsgálati eredmé-nyek alapján 22,5% és 18,1%-ban fejlődött ki mérsékelt gastrointestinalis mellékhatás a hagyományos és hipofrakcionált módon sugárkezelt vizsgálati csoportokban.…”
Section: Akut éS Késői Gastrointestinalis Toxicitás (Normofrakcionáláunclassified
“…Hoffman [42] elemzésében a normálfrakcioná-lású IMRT-kezelés esetében 16,5%-ban, míg a hipofrakcionálású IMRT-kezelés esetén 15,8%-ban alakult ki mérsékelt vagy súlyos urogenitalis toxicitás. Pollack [41] közleményében a hagyományos frakcionálású ágon 13,4%-ban, míg hipofrakcionálás esetén 21,5%-ban alakult ki késői urogenitalis toxicitás.…”
Section: Akut éS Késői Urogenitalis Toxicitás (Normofrakcionálás Vs unclassified